Using peer-mentoring to increase clinical skills in physiotherapy education - Alves Lopes, António (2022)
Purpose / hypothesis: The aim of this study was to compare 3 different approaches to Peer-Mentoring in relation to the perception of the students how Peer-Mentoring could promote the development of Physiotherapy clinical skills in undergraduate Physiotherapy students. Subjects: This Peer-Mentoring was developed among students of the 2nd and 3rd years of undergraduate Physiotherapy course Material / Methods: During one semester, the students of the second year were organized in small groups and distributed to them a group of mentors of the third year. Each mentor had a specific area and a specific mentoring style. Orientation support was given at least 3 times during this process. All the groups registered all the activities carried out in the meetings. An online questionnaire was developed and used to perceive perceptions about the outcomes and satisfaction of all participants in the mentoring process Results: The main results of the questionnaire showed great satisfaction with the mentoring process in both groups. The students refer to the importance that the tutor had in consolidating theoretical knowledge, clinical reasoning and practical skills. Both groups expressed that the process was very rewarding and are eager to repeat this experience. Regarding the comparison between mentoring styles, students preferred mentoring with more directed than free styles. Conclusions: Mentoring promotion facilitates learning opportunities for 2nd graders in the topics covered and can also increase the leadership and teaching skills of 3rd graders, both outcomes have the potential to benefit elements outside this process, including future work or patients. In relation to the process of Peer-Mentoring a good organization and objectives/tasks well established by the responsible teacher seems to be fundamental to the overall success. The promotion of peer-mentoring could facilitate peer-to-peer learning opportunities for students, and promote leadership and teaching skills.